Strategi Kepala Sekolah Dalam Pengelolaan Penerimaan Peserta Didik Baru Di SDN 24 Peusangan - T. M. Haekal; Marzaniar, Putri; Azmi, Khairul; Idris, M. Irwan; Luddin, Faisal (Educompassion: Jurnal Integrasi Pendidikan Islam dan Global, 2024)
Increasing the number of new students in an institution requires effective and targeted management. This study aims to analyze the strategies employed by the school principal in managing the New Student Admission (PPDB) process at SDN 24 Peusangan and its impact on the quality of admissions and school success. The research uses a descriptive qualitative approach, employing in-depth interviews and document analysis as data collection methods. The findings show that the principal's strategy in PPDB, which involves extracurricular activities and a zoning system, positively contributes to the increase in new student enrollment. However, there are some weaknesses, such as suboptimal socialization and technical issues with the online system. Despite these challenges, the principal’s strong vision and decision-making ability positively affect the selection process and the quality of educational services at the school.